2015
DOI: 10.1155/2015/538752
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Fuel and Reactor Design for Platinum Nanoparticle Catalyzed Microreactors

Abstract: Typical microcombustion-based power devices entail the use of catalyst to sustain combustion in less than millimeter scale channels. This work explores the use of several other candidate fuels for ~8 nm diameter Pt particle catalyzed combustion within 800 μm channel width cordierite substrates. The results demonstrate while commercial hydrocarbon fuels such as methane, propane, butane, and ethanol can be used to sustain catalytic combustion, room temperature ignition was only observed using methanol-air mixtur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Vican et al designed a ceramic Swiss-roll combustor with a platinum-catalyzed central section, which was sandwiched between two TEG modules on either side to deliver electric power. The coupling of catalytic combustion with TEGs was also investigated for various hydrocarbons to exploit the properties of low-temperature ignition. …”
Section: Introductionmentioning
confidence: 99%
“…Vican et al designed a ceramic Swiss-roll combustor with a platinum-catalyzed central section, which was sandwiched between two TEG modules on either side to deliver electric power. The coupling of catalytic combustion with TEGs was also investigated for various hydrocarbons to exploit the properties of low-temperature ignition. …”
Section: Introductionmentioning
confidence: 99%
“…Pt-based nanoparticles with controlled morphology, structure and composition are catalytically active for both anodic (methanol oxidation reaction, MOR) and cathodic (oxygen reduction reaction, ORR) reactions of the direct proton exchange membrane fuel cells (PEMFCs) [1,2]. Similarly, Pt-based nanoparticles have numerous applications [3] such as a catalyst [4,5], in car exhaust systems [6,7], gas sensors [6], glucose sensors [8] and cancer therapy [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[11] showed that the catalysis of propane fuel in platinum coated microchannel investigated blowout limits under varying pressure conditions. Platinum nanoparticles were explored to catalyze multiple fuels of hydrocarbon fuels such as propane, butane and methane in an attempt to study the behaviour of reactants under the catalysis sustained combustion processes [12]. [13] presented numerical modelling of the chemical process of combustion based on Arrhenius assumptions, gas flow based on the Navier-Stokes equation and the Maxwell-Stefan equation was used to capture the concentration and temperature dependence of various species diffusivities.…”
mentioning
confidence: 99%